Tissue-specific transcriptome responses to Fusarium head blight and Fusarium root rot - Haidoulis, John Francis; Nicholson, Paul (Frontiers in Plant Science, 2022)
Fusarium head blight (FHB) and Fusarium root rot (FRR) are important diseases of small-grain cereals caused by Fusarium species. While host response to FHB has been subject to extensive study, very little is known about response to FRR and the transcriptome responses of FHB and FRR have not been thoroughly compared. Brachypodium distachyon (Bd) is an effective model for investigating host responses to both FHB and FRR. In this study the transcriptome response of Bd to F. graminearum (Fg) infection of heads and roots was investigated. An RNA-seq analysis was performed on both Bd FHB and FRR during the early infection. Additionally, an RNA-seq analysis was performed on in vitro samples of Fg for comparison with Fg gene expression in planta. Differential gene expression and gene-list enrichment analyses were used to compare FHB and FRR transcriptome responses in both Bd and Fg. Differential expression of selected genes was confirmed using RT-qPCR. Most genes associated with receptor signalling, cell-wall modification, oxidative stress metabolism, and cytokinin and auxin biosynthesis and signalling genes were generally upregulated in FHB or were downregulated in FRR. In contrast, Bd genes involved in jasmonic acid and ethylene biosynthesis and signalling, and antimicrobial production were similarly differentially expressed in both tissues in response to infection. A transcriptome analysis of predicted Fg effectors with the same infected material revealed elevated expression of both core tissue-independent genes including cell-wall degradation enzymes and the gene cluster for DON production but also several tissue-dependent genes including those for aurofusarin production and cutin degradation. This evidence suggests that Fg modulates its transcriptome to different tissues of the same host.